PENGARUH PEMBAGIAN KERJA DAN KOMUNIKASI TERHADAP STRES KERJA KARYAWAN PADA PT. PERDANA JAYA TUNGGAL PERKASA DENPASAR - Maria Advensena Klara Kato (Majalah Ilmiah Widyacakra, 2019)
This research aims to determine the effect of the division of labor and communication partially or simultaneously on the work stress of employees at PT. Perdana Jaya Tunggal Perkasa Denpasar. The sample used is all employees of PT. Perdana Jaya Tunggal Perkasa Denpasar based on boring sample method. Data collection methods used were observation, questionnaires, and study documentation. The analysis technique used in this study, including descriptive analysis, analysis prerequisite test, classic assumption test, multiple linear regression analysis, t test, and F test analysis. Based on the results of the study showed that through the t test it is known that the division of labor variables and communication variables each have a partial effect on employee work stress with a value of 3.565 > ttable 1.996 and tcount 2.898 < t table 1.996. While the results of Fcount > Ftable (52,613 > 2,74) it is stated that there is a simultaneous influence between the variables of work division (X1) and communication (X2) influencing employee work stress (Y) with a determination coefficient of 61.1%.